FIELD EFFICACY STUDY OF DIFFERENT BIORATIONALS AND INSECTICIDES AGAINST BRINJAL SHOOT AND FRUIT BORER (Leucinodes orbonalis Guenee) UNDER TERAI REGION OF WEST BENGAL - SARKAR, SURAJ; PAL, SUPRAKASH; SAHOO, SHYAMAL; LASKAR, NRIPENDRA; GHOSH, JOYDEB (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
At the Uttar Banga Krishi Viswavidyalaya's teaching farm, field tests were conducted on brinjal during the rabi seasons of 2018–2019 and 2019–2020 to assess the field efficacy of seven biorationals and insecticides against Leucinodes orbonalis Guenee, which infests brinjal (Solanum melongena L.). Results showed that Chlorantraniliprole 18.5 SC, Flubendiamide 39.35 SC, and Novaluron 5.25% + Emamectin Benzoate 0.9% SC were the most successful treatments in terms of lowest shoot infestation (2.24-6.05%) and fruit infestation (number basis: 11.01-13.29% and weight basis: 11.94-15.75%). Bacillus thuringiensis var. kurstaki and Chlorantraniliprole 18.5 SC both produced the highest commercial fruit yields, ranging from 13.54 to 14.54 t/ha and 14.11 to 14.51 t/ha, respectively. Azadirachtin 50,000 ppm was found to be the least effective compound against brinjal shoot and fruit borer.